Study on the Effect of Partial Ti Substitution at Zn Sites on the Structural, Electronic, and Magnetic Properties of Zn3P2 - G. Jaiganesh; S. Mathi Jaya (Recent Trends in Chemical and Material Sciences Vol. 3, 2021)
Using the ab-initio calculations based on density functional theory, we have investigated the structural, electronic, and magnetic properties of the Ti-substituted Zn3P2 compound. One/Two Ti atom replacements in the unit cell of Zn3P2 containing eight molecules per formula unit (40 atoms) are considered in the study. Our results show that the ferromagnetic phase is favored for the single Ti atom substitution. The total energy corresponding to the ferromagnetic phase is lower than that of the nonmagnetic phase. A considerable value of the magnetic moment at the Ti site is obtained from our calculations. These compounds may be useful to spintronic applications, and we hope this study motivates others to further investigate about these compounds.